Should procalcitonin be included in acute cholecystitis guidelines? A systematic review - Yaow, Clyve Yu Leon (2024)
Background and Objectives: Acute cholecystitis (AC) is a common surgical emergency. Recent evidence suggests that serum procalcitonin (PCT) is superior to leukocytosis and serum C-reactive protein in the diagnosis and severity stratification of acute infections. This review evaluates the role of PCT in AC diagnosis, severity stratification, and management. Materials and Methods: PubMed, Embase, and Scopus were searched from inception till 21 August 2022 for studies reporting the role of PCT in AC. A qualitative analysis of the existing literature was conducted. Results: Five articles, including 688 patients, were included. PCT ≤ 0.52 ng/mL had fair discriminative ability (Area under the curve (AUC) 0.721, p < 0.001) to differentiate Grade 1 from Grade 2-3 AC, and PCT > 0.8 ng/mL had good discriminatory ability to differentiate Grade 3 from 1-2 AC (AUC 0.813, p < 0.001). PCT cut-off ≥ 1.50 ng/mL predicted difficult laparoscopic cholecystectomy (sensitivity 91.3%, specificity 76.8%). The incidence of open conversion was higher with PCT ≥ 1 ng/mL (32.4% vs. 14.6%, p = 0.013). A PCT value of >0.09 ng/mL could predict major complications (defined as open conversion, mechanical ventilation, and death). Conclusions: Current evidence is plagued by the heterogeneity of small sample studies. Though PCT has some role in assessing severity and predicting difficult cholecystectomy, and postoperative complications in AC patients, more evidence is necessary to validate its use.